2005
DOI: 10.1080/10256010500230072
|View full text |Cite
|
Sign up to set email alerts
|

Isotope characteristics of vegetables and wheat from conventional and organic production

Abstract: Multielement isotope ratio analysis was checked for its suitability as a means for the discrimination between agricultural products from integrated/conventional or organic production, respectively. Differences were mainly found for delta15N-values. Paprika and tomatoes from organic production in greenhouses showed delta15N-values above+7 per thousand, whereas corresponding products from conventional cultivation had delta15N-values near 0 per thousand. Lettuce, onions, cabbage and Chinese cabbage from field pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
66
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 11 publications
14
66
0
1
Order By: Relevance
“…+5 and +9%, while those grown with hornmeal (+6.0%) made of animal horn and hoofs had d 15 N values between +6 and +10%. These overlapping values may be attributed to 15 N enrichment of N derived from synthetic fertilizer through N loss via NH 3 volatilization and denitrification (Schmidt et al 2005). It has clearly been demonstrated that 15 N enrichment in plant tissues is directly related with N losses that increase d 15 N of the N remaining in the soil due to N isotopic fractionation (e.g., Johannisson and Högberg 1994).…”
Section: Plant Growth and N Uptakementioning
confidence: 98%
See 1 more Smart Citation
“…+5 and +9%, while those grown with hornmeal (+6.0%) made of animal horn and hoofs had d 15 N values between +6 and +10%. These overlapping values may be attributed to 15 N enrichment of N derived from synthetic fertilizer through N loss via NH 3 volatilization and denitrification (Schmidt et al 2005). It has clearly been demonstrated that 15 N enrichment in plant tissues is directly related with N losses that increase d 15 N of the N remaining in the soil due to N isotopic fractionation (e.g., Johannisson and Högberg 1994).…”
Section: Plant Growth and N Uptakementioning
confidence: 98%
“…In a similar fashion, the stable C isotope ratio ( 13 C/ 12 C, expressed as d 13 C ) of crop tissues in conventional and organic farming system has been explored by a few researchers (Nakano et al 2003;Georgi et al 2005;Schmidt et al 2005). They hypothesized that plants under contrasting farming systems (conventional vs. organic) may have different d 13 C as plant d 13 C is an integrator of gas exchange response to different environmental conditions associated with water and nutrient stresses (Choi et al 2005a).…”
Section: Introductionmentioning
confidence: 97%
“…17,18,22,23 In our previous study, the overlapped δ 15 N values were observed in Brassica campestris with combined application of organic and synthetic fertilizers. 17 Some reports drew a conclusion that 15 N isotope analysis could only be used to determine whether chemical fertilizer had been singly applied.…”
Section: ■ Introductionmentioning
confidence: 94%
“…22 Thus, δ 15 N value could be used as a rough organic marker only in the case of single fertilizer application. 23 It is necessary to employ a statistical methodology to classify a randomly analyzed "off the shelf" sample as organic/conventional.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…If we assume that both ethynyl carbon atoms in EE 2 are petrochemical, the plant-based precursor compounds must also contain some fossil carbon atoms. These fossil carbons are probably derived from CO 2 amendments to commercial greenhouses from natural gas heating exhaust [22,23] and/or from plants grown in areas heavily impacted by fossil fuel emissions. [24] It is interesting to note that Eglinton et al [25] found a similar 14 C content (Δ 14 C = -113 %) in a sample of Crassula argentea grown in a greenhouse heated by natural gas.…”
mentioning
confidence: 99%